The influence of employer's behaviour, communication and psychological ownership in the SMEs - Mansor, Zuraina; Amdan, Siti Amifah (International Foundation for Research and Development, 2015)
Small and medium-sized enterprises (SMEs) can be deceptively complex organizations to manage due to a broad range of challenges, such as issues relating to owner-managers, as well as employees and the employment relationship (Mallett & Wapshott, 2012). This study is conducted to study three factors, the behavior of the employer, the influence of communication and psychological ownership with relevant to promoting employee and employer relationship in the SMEs. Questionnaires were distributed to 150 employees of various SMEs in the Sri Serdang area of Selangor, Malaysia. The result was analyzed using the descriptive and correlation analysis.